MEDIA RELATIONS MANAGEMENT OF PRIVATE UNIVERSITY IN SUPPORTING REPUTATION ENHANCEMENT - Anggarina, Paula Tjatoerwidya; Irawan, Agustinus Purna; Dewi, Fransisca Iriani Roesmala; Noviyanto, Noviyanto; Putri, Dhita Widya (International Journal of Application on Economics and Business, 2024)
The reputation of private university is important factor to win the competition. One of the public relations (PR) communication activities to build reputation is media relations. The purpose of this study is how to manage media relations by private university in building reputation through PR. The research method uses a descriptive qualitative method, which combines surveys using questionnaires, interviews, and Focus Discussion Groups (FGD) focusing on the form of media relations activities, information content that has publication value, and communication channels used to support reputation enhancement. The results showed that media relations are very important and useful in supporting the reputation of private university. The forms of media relations activities that can be carried out are press conference, media gathering, news coverage, media visit, and doorstop. The use of effective communication channels in delivering information to the public is online media, social media, radio, websites, and television. Campus news content that has publication value is academic achievement, solutions to problems in society, ranking, accreditation, research, achievement of Key Performance Indicators, and community service activities. The results of this study will be one of the references in further research.